'Things seen and unseen': the logic of incarnation in Merleau-Ponty's ontology of flesh - Edgar, Orion (2012)
My thesis here is that Merleau-Ponty’s ontology of flesh, in its development, suggests a logic of incarnation which carries philosophical ontology beyond entrenched dualisms, and offers to Christian theology a route away from dualistic compromises and back to its own deepest insight. I set out first to develop Merleau-Ponty’s fleshly ontology by tracing its roots in his early thought on the reversibility of perception, which installs the perceiver at the heart of a world with which he is engaged and on which he depends; this relationship is grounded in the elemental faith of perception. I develop this perceptual understanding with reference to eating as a mode of perception; hunger joins our biological needs to their imaginative development, and Man, the hungry animal, transforms his desire, and thus his world. I show how dualistic ontologies are grounded in a geometrical conception of nature which founds a notion of God as removed from the world in the absolute distance of the geometer from geometry, and argue that this mathematisation of nature is hypostasised in the modern understanding of vision. I develop a counter-understanding which liberates the seer from his incarceration in immobility, emphasising that sight depends on movement and on its imbrication with the other senses, involving us in a world of existential significance, and suggesting a partial recovery of the extramission and species theories of sight. I then argue that nature must be understood in terms of place, rather than as a spatiotemporal container. There is a fundamental man-nature chiasm which precedes analysis. Incarnation is not an insertion into nature but a flowering within it of a fundamental logos. This grounds metaphysics in the perceived world, affirming meaning within contingency. For a Christian theology rooted in such a notion of incarnation, God is revealed in the depths of nature and history.